REDESIGN PULVERIZER SHAFT UNIT 2 DI PLTU SEKTOR BUKIT ASAM 4 X 65 MW - Hardyanto, Arief Prakoso; Mangestiyono, Wiji; Darmanto, Seno; Murni, Murni (universitas teuku umar, 2022)
In the operation of the Bukit Asam power plant, in all generating units there are many disturbances that can cause derating the units. Derating of the unit can occur due to decrease in the performance of the steam turbine, decrease in the reliability of the pulverizer, and also disturbances in the coal supply system and various factors. Based on the performance data of the Bukit Asam Generation Sector (Monthly disturbance report) in January 2014, there were 54 derating disturbances recorded. One of the causes of the derating was a broken Pulverizer Shaft with a loss of operating hours for 196.78 [hours] which caused an unallocated electricity loss of 12,422 [GWh]. With the realization of AFI (Action For Improvement) in this final project creation assignment, it aims to redesign the shaft pulverizer, as well as analyze the causes of the pulverizer shaft break. By redesigning the pulverizer shaft and analyzing the cause of the pulverizer shaft breaking, it was found that the cause of the fracture of the shaft made from AISI 1045 with the old design was from calculating the shear stress value of 48.44 x 107 [N/m2], this result exceeded the value of the material permit voltage of 31.8 x 107 [N/m2], so it was not safe to use and the service life was not long. The results of the redesign shaft changed the dimensions of the diameter of the shaft head which was previously 0.174 [m] in diameter to a dwelling of 0.25 [m]. The results of calculating the redesign shaft made from AISI 1045 obtained a shear stress value of 16.33 x 107 [N/m2], this result is smaller than the material clearance voltage value of 31.8 x 107 [N/m2], so it is safer with a relatively longer service life.Keywords: Derating, Pulverizer Shaft, material, Redesign, Shear Stress